Kejahatan yang Berkembangan dalam Masyarakat - Kasihani Giawa; Penataran Lase; Hendrikus Otniel Nazaro Harefa (International Forum of Researchers and Lecturers, 2025)
Crime is a social phenomenon that is always developing along with changes in society. This study aims to examine various forms of crime that develop in society and the factors that influence them. Through a qualitative approach with observation techniques, interviews, and documentation studies, this study reveals that crime is not only due to economic motives, but is also influenced by weak law enforcement, shifting social values, and lack of social supervision, types of crimes found include theft, drug abuse, domestic violence, and technology-based crimes, The results of this study are expected to contribute to efforts to prevent and overcome crime effectively in society